Crear estrategias publicitarias para la promoción de la corporación de productores agropecuarios maiceros del cantón Pindal, (corpap), provincia de Loja, periodo enero-marzo de 2014. Propuesta alternativa - VERA QUITO, JOSÉ PAÚL (2015)
This research focuses on a thorough study of the problem called "Creating advertising strategies for the promotion of the Corporation of Agricultural Producers Canton maiceros Pindal (CORPAP), province of Loja" from January to March period of 2014. Alternative Proposal , demonstrating the problem from the time of observation for which it was stated that the Internet is dominating all forms of communication in the world. Both overall and specific objectives were checked by field work, because everyone agrees that it should have an alternative space to promote and report a series of activities that the organization develops. What it is represented in statistical tables and charts with their analyzes and interpretations. The scientific and statistical methods helped to collect information to provide logical support to the study. So did the surveys and interviews, be concluded that the image projected outward maiceros Association is bad, therefore does not project any kind of interaction between partners, permeate with potential clients or customers of the grass, by it is recommended to managers of the Group are required to develop messages that are intended to recover the corporate image of the same, achieving processes of interrelation and interaction between its members and their customers. It further concludes that the advertising strategies employed by the association of corn growers Pindal are negative when the processes of interaction and social interaction are limited and that the Association does not have a digital instrument that allows promoting its activities, especially to achieve commercialize existing corn production at the site, and to help recover the image of the organization at the consumer level, among the recommendations are: to suggest to the directors of the Association of Canton maiceros Pindal find the best advertising strategies to through electronic means in order to achieve positioner to the entity in the market and design a digital communication tool as a blog that will become an indispensable resource to achieve promotion to the organization based on their interests in order to raise awareness the products we offer.